'For You Will (Still) Be Here Tomorrow': The Many Lives of Intergenerational Equity. Issue 1 (9th March 2023) - Bertram, Daniel
Abstract: This article traces the various legal incarnations of the intergenerational equity principle. Despite its silent proliferation in international and constitutional laws over the past five decades, the principle dwelled mostly at the margins of inquiry and practice. Recent efforts to counteract global warming have allowed intergenerational claims to gain new traction. Building on a comparison of ten climate-related lawsuits, I analyze the latest advances in the representation, conceptualization, and remediation of future generations' interests. Against the backdrop of growing willingness to engage with intergenerational disputes, legal decision makers will need to confront two thorny challenges going forward. Firstly, evolving doctrines of extraterritoriality and legal subjecthood increasingly require the protective scope of the principle to extend to foreign citizens and non-human persons. Secondly, awareness of dispersed and interlocked long-term risks may trigger the application of intergenerational doctrines beyond a narrow environmental frame. Grappling with these challenges implicates larger reflections about the role of law in contriving our collective future.